Fluorescence based detection of bioaerosols to improve emissions characterization from environmental sources - Nasir, Zaheer A.; Tyrrel, Sean F. (The Aerosol Society, 2015)
Bioaerosols are ubiquitous in ambient air but there have been increasing concerns about their human exposure and to health impact due to ever increasing environmental emissions from sources such as biowaste and intensive agriculture facilities (Borlée et al. 2015). However, the knowledge on their risk of exposure to the public is limited mainly due to a lack of emission characterisation, in part due to the limitation of conventional methods for the detection and characterisation of ambient bioaerosols. Among emerging techniques, fluorescence spectroscopy has shown promise in detecting and broadly classifying bioaerosols (Pan et al. 2015). This paper provides the preliminary results of a study that aims to demonstrate the potential of a fluorescence based bioaerosol sensor unit to detect and quantify these in real time with a view to developing and advancing bioaerosol exposure assessment methodologies to various environmental sources.